Microstructure, adhesion and erosion properties of Fe-Cr-Ti-Mo-C-Si coating with varying Titanium. (March 2021) - Sharma, Ratnesh Kumar; Das, Randip Kumar; Kumar, Shiv Ranjan
Highlights: Formation of hardened Fe2 Ti phase enhanced mechanical and wear properties. Increase in titanium content improved the micro-hardness and adhesion pull off strength. Role of impact velocity and impingement angle is analyzed. Abstract: The purpose of this study was to investigate the effect of titanium content on the microstructure, surface morphology, micro-hardness, adhesion and erosion properties of fabricated Fe alloy based coating materials. In this regard, Fe alloy based coating materials consisting of Fe, Mo, Si, C, Cr with varying Ti content were fabricated by High Velocity Oxygen fuel (HVOF) coating process. XRD results confirmed the formation of hardened Fe2 Ti phase. Increase in 5 wt. % of titanium in the Fe based coating material increased the hardness and adhesion pull off strength by 20 % and 33 % respectively. The erosion wear rate of coating material was increased with the increase in impact velocity. However, in case of impingement angle, the erosion wear rate was increased for the increase in impingement angle from 0 to 60° but later decreased at 90°. The trend was attributed to the fact that erosion wear at impingement angle 60° was mainly influenced by micro-cutting erosion mechanism by normal and shear stresses but at impingement angle at 90°, the erosion wear rate mainly depends upon plastic deformation only due to normal stress.